IS EMPLOYEE PERFORMANCE INFLUENCED BY DISCIPLINE, MOTIVATION, AND COMPETENCE? A STUDY ON SALON AND BEAUTY EQUIPMENT BUSINESS - Manafe, Leonard Adrie; Wahib, Moh; Zebua, Martin; Andriana, Ririn; Erawati, Yourini (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The research conducted to know the discipline, motivation and competencies impacted on performance of employee at Evy Beautrec (